A Smart Home Platform and Hybrid Indoor Positioning Systems for Enabling Aging in Place - Ianovski, Alexandre (My University, 2018)
Activities of daily living (ADLs) are everyday routine tasks which provide insight into the physical and cognitive wellbeing of older adults. ADLs are commonly self-reported to clinicians, which can lead to overestimation and underestimation of a patients’ functional abilities. Remote health monitoring is an emerging field aimed at utilizing technology for monitoring ADLs remotely, improving clinical accuracy and enabling older adults to age safely within their homes. In this dissertation, we report a Smart Home platform and two indoor positioning systems (IPSs) – (i) a hybrid Bluetooth Low Energy (BLE) and radar motion sensor system and (ii) a hybrid radio-frequency identification (RFID) and infrared (IR) range-finding system for tracking occupant mobility, the primary predictor of falls among older adults. For the Smart Home platform, the design methodology and technological features were explained. As for the IPSs’, position accuracy of multiple occupants within multiple rooms of a residential apartment was evaluated. The systems were also evaluated for cost, implementation ease, and scalability, which, upon reviewing literature, were identified as key metrics for developing an IPS for enabling aging in place. Both IPSs enforced a decentralized localization architecture and performed well, achieving high localization accuracy for multiple occupants.
SMART HOME AND INDOOR POSITIONING SYSTEMS FOR AGING IN PLACE
Keywords: Smart Home; IoT; Health Monitoring; Indoor Positioning; IPS; Aging in place